Defining Rape: The Problem with Consent - Adoch, Caroline (Strathmore Law Journal, 2022)
Rape is one of the most commonly reported crimes all over the world. It is a crime under both international and national law although it is still primarily prosecuted before domestic courts. The traditional common law definition of rape articulates three elements of the crime of rape; vaginal penetration, lack of consent and direct participation of the accused person. However, many jurisdictions are moving away from consent-based definitions of rape. Through a feminist lens, this paper explores the place of consent as an element of the crime of rape. It undertakes a comprehensive review of literature and case law and makes an analysis of the articulation of consent as an element of the crime of rape at both national and international levels. It establishes that the legal definition of rape has a significant impact on the prosecution of rape cases and on the victim of rape. If the definition is based on the need for the prosecution to prove the lack of consent, then the legal process is focused on her behaviour and reaction to the sexual assault. It concludes that a definition of rape based on lack of consent is problematic and hinders access to justice for rape victims and it is inconsistent with the contemporary understanding of rape as a crime of sexual violence.